Application de Ia methode des derivees d’ordre eleve a l’optimisation de structures - Beley, Jean-Daniel; Broudiscou, Claude; Guillaume, Philippe; Masmoudi, Mohamed; Thevenon, Frederic (European Journal of Computational Mechanics, 1996)
In shape optimization problems the use of higher order derivatives leads to an explicit Taylor’s expansion of the cost function, obtained from only one finite element analysis. The automatic differentiation provides exact derivatives of the discrete problem and its additional cost is low with respect to the cost of a finite element analysis. Two industrial examples in linear elasticity show the interest of this new method.